PENGARUH TIKTOK TERHADAP NIAT BERKUNJUNG WISATAWAN NUSANTARA KE WHITE ROCK BEACH CLUB PANTAI MELASTI - Ekaviati, Ni Ketut Noviani; Wijaya, NMS.; Mahadewi, NPE. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024)DO - 10.24843/IPTA.2024.v12.i01.p14, 2024)
Tiktok is a social media that is currently popular and widely used in Indonesia with the existence of TikTok growing rapidly with the number of users continuing to increase with an increase of 109.9 million TikTok users in early 2023. One of the beach clubs visited by many TikTok users is White Rock Beach Club. The purpose of this research is to determine the results of the influence of TikTok social media on domestic tourists' intention to visit the White Rock Beach Club.This research method uses mixed methods data analysis techniques which include quantitative descriptive analysis, qualitative descriptive analysis and simple regression analysis. The technique for determining informants was taken by purposive sampling with a sampling technique using the Slovin formula with a total of 86 respondents with the criteria of domestic tourists visiting the White Rock Beach Club. Data collection techniques were carried out through observation, interviews, literature study, questionnaires and documentation. Testing in this research uses validation tests, reliability tests, data normality tests, linearity tests, heteroscedasticity tests, t tests, and coefficient of determination tests with data processing tools using SPSS. The results of this research show a significance value of 0.000, less than 0.05 (0.000 < 0.05), with a regression coefficient value of 0.788 and a calculated t value > t table (28.999 > 1.988). These results mean that social media has a positive influence on the intention to visit Indonesian tourists to White Rock Beach Club, Melasti Beach.